Evaluation of water table fluctuations and drainage discharge of bi-level drainage system in a layered soil - S. M. A. Maddahzadeh.; k, Esmaili; B. Ghahraman (علوم آب و خاک, 2017)
Bi-level drainage system is a type of underground drainage systems, in which adjacent drainage lines are installed at different depths. In the Hydraulics Laboratory, Ferdowsi University of Mashhad, a model was built, that include a cube tank 2 meters in length, width and height of 1 meters was made ​​of galvanized. In this model, two rows 20 cm apart from each other drains were installed. As drainage, a pipe of three layers to the outer diameter of 16 mm was made of PVC. Within this model of stratified soil was used as a soil layer of low permeability with a hydraulic conductivity of 1.15 cm per hour, thickness of 20 cm soil layer between two light soil layer with 30-cm thickness for bottom layer and 20 cm for the top layer with a hydraulic conductivity of 1.55 cm per hour. For accurate measurement of the water table Behavior in the soil at each point of the model, some piezometer distance of 10 cm from each other on the floor model was installed. After Outfit of model with blow-off valve, Experiments with a heavy irrigation for different intervals between depths of 30 and 50 cm were used in drainage and water table elevation values ​​as observed values ​​were extracted from the model. The results show that the values ​​obtained from Upadhyaya and Chauhan Equation only in small area of water table profiles, which include an area of between the two drainage, are consistent with observed and with a wider distance between deep and shallow drainage, time of drop in water table increased.